Penerapan Metode AHP-Fuzzy untuk Mengukur Pemahaman Penyedia Jasa Konstruksi terhadap Sistem E-Tendering di Kota Surabaya - Fahreza Irghi Budi Saputra; Michella Beatrix (Prosiding Seminar Nasional Ilmu Teknik, 2025)
E-Tendering is an electronic-based procurement method that integrates all parties involved in construction projects through a digital platform, simplifying communication, document exchange, and transactions from the initial stage to project completion. The primary objective of implementing E-Tendering in the construction sector is to improve efficiency and transparency in the procurement process of goods and services. However, construction service providers often face obstacles in E-Tendering, such as limited technological proficiency, administrative errors that may disqualify bids, and technical issues like internet connectivity and platform system reliability. Therefore, this research aims to identify the barriers and level of understanding of E-Tendering among construction service providers in Surabaya. A total of 51 respondents were selected using snowball sampling, based on their participation in the E-Tendering system. Data processing in this study employed a quantitative approach using the Fuzzy AHP method to analyze the criteria and sub-criteria related to understanding and obstacles in participating in electronic construction service tenders (E-Tendering). The results of the analysis of service providers’ understanding of the E-Tendering system using the AHP method showed a λmax value of 9.09, a Consistency Index (CI) of 0.01, and a Consistency Ratio (CR) of 0.007. The CR value, which is far below the threshold of 0.10, indicates that the respondents’ assessments are consistent, meaning that the pairwise comparison results of the nine criteria can be considered valid and reliable.